2000
DOI: 10.1002/(sici)1097-4636(200005)50:2<144::aid-jbm8>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-carrying polystyrene to mediate cellular attachment and growth via interaction with growth factors

Abstract: Various sugar-carrying polystyrenes (PSs), which consist of synthetic styrene and sugar moieties, are glycoconjugates that are able to attach to polymeric surfaces. Heparin-carrying PS (HCPS) is especially able to retain the binding of heparin-binding growth factors (GFs) such as vascular endothelial GF 165 (VEGF(165)) or fibroblast GF 2 (FGF-2). Human skin fibroblast cells, human coronary smooth muscle cells, and human coronary endothelial cells have good adherence to the HCPS-coated plate. The growth rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…In addition, immobilization of Hep onto Matrigel was important for the inhibitory effect of NAC-HCPS on tumour cell adhesion to Matrigel. As we reported previously, NAC-HCPS is effectively adsorbed to various polymeric surfaces (Ishihara et al, 2000a), collagen (type I)-substratum (Ishihara et al, 2001) and Matrigel (data not shown) through a hydrophobic interaction between the hydrophobic surface and polystyrene core of NAC-HCPS. And cell adhesion of tumour cells (B16 and 3LL) were similarly inhibited by immobilisation of NAC-HCPS on the Matrigel (data not shown).…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…In addition, immobilization of Hep onto Matrigel was important for the inhibitory effect of NAC-HCPS on tumour cell adhesion to Matrigel. As we reported previously, NAC-HCPS is effectively adsorbed to various polymeric surfaces (Ishihara et al, 2000a), collagen (type I)-substratum (Ishihara et al, 2001) and Matrigel (data not shown) through a hydrophobic interaction between the hydrophobic surface and polystyrene core of NAC-HCPS. And cell adhesion of tumour cells (B16 and 3LL) were similarly inhibited by immobilisation of NAC-HCPS on the Matrigel (data not shown).…”
Section: Discussionsupporting
confidence: 76%
“…Periodate-oxidised (IO 4 -) Hep and periodate-oxidised, alkaline-degraded low molecular weight (IO 4 -LMW-) Hep (Fransson and Carlstedt, 1974;Fransson, 1978) are known for not having a specific pentasaccharide structure to interact with antithrombin III (Conrad and Guo, 1991), and therefore its anti-coagulant activity (APTT and PT) is much lower than Hep (Figure 2). We previously reported the preparation of NAC-HCPS using the IO 4 -LMW-Hep (Ishihara et al, 2000a). In this study, we have demonstrated that NAC-HCPS inhibits subcutaneously induced tumour growth and metastasis to lung of B16 melanoma and 3LL (Lewis lung cancer) cell line.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations